2021
DOI: 10.1002/1348-9585.12249
|View full text |Cite
|
Sign up to set email alerts
|

Association between occupations and selected noncommunicable diseases: A matched case-control among Thai informal workers

Abstract: Objectives:We conducted a matched case-control study of informal workers to determine the association between occupational classification and selected types of noncommunicable diseases (NCDs). Method: We extracted data of patients aged ≥18 years from the Thai National Health Security Office database (NHSO) during 2011-2014. Cases were patients who had a primary diagnosis of: diabetes mellitus (E10-E14), hypertension (I10-I15), ischemic heart disease (I20-I25) or stroke (I60-69), or thyroid gland disorder (E00-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…There were also differences in the awareness rates among different occupational groups, which is consistent with the results reported in Handan City and other places [ 26 ], suggesting that different forms of health education activities should be adopted according to the occupational characteristics of various groups of people [ 27 , 28 ]. A study on the nutrition and health knowledge of Wuhan residents showed that medical workers and educators tend to know more about nutrition than other professions [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…There were also differences in the awareness rates among different occupational groups, which is consistent with the results reported in Handan City and other places [ 26 ], suggesting that different forms of health education activities should be adopted according to the occupational characteristics of various groups of people [ 27 , 28 ]. A study on the nutrition and health knowledge of Wuhan residents showed that medical workers and educators tend to know more about nutrition than other professions [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with studies from Kenya 30 and Thailand. 31 The association could be explained from the perspective that women who are employed have a higher tendency to engage in high-risk dietary behaviours including high salt intake and low vegetable consumption. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Data from the Indonesian House Health Survey conducted in 2018 found that the prevalence of hypertension in farmers/laborers/fisherman tends to be higher than in other occupations [4]. However, in Thailand, unskilled workers were found to have a significantly higher risk for hypertension compared to agricultural workers [16], and there was not significant difference in rates of abnormal blood pressure between organic and conventional (pesticide using) farmers [17].…”
Section: Introductionmentioning
confidence: 99%